College’s Internship Program as A Form of Experiential Learning and Its Effect towards Students’ Skill - Heriani Dhia Ayu Safitri; Achmad Supriyanto; Ahmad Yusuf Sobri (IJEEM - Indonesian Journal of Environmental Education and Management, 2022)
The available future jobs have become one of the main concerns especially for fresh graduate. This may be the case at times that there is still high unemployment in Indonesia which has dynamic geography, variety labour force, and diverse economy. As a form of experiential learning in higher education, internship program is held to meet the needs of a developing world. This article will focus on how the internship program can be beneficial to help the students in preparing to be ready to compete in labour market. In order to answer research question, the researcher used descriptive qualitative approach with data collection technique in the form of literature review. The result shows that internship program can significantly affect students’ skill. An internship gives students with real-world experiences in a social learning setting. Considering the available future jobs have become one of the main concerns especially for fresh graduate, university should pay more attention on how their internship program can be more effective to help the intern to train their skill which cannot be learnt in classroom environment.